Modern Medicine and the Right to Die: Issues of Illness, Treatment, and Death in the Modern Era - Amr Osman (Al-Jami'ah Research Centre, 2026)
The development of modern medicine, with its immense capabilities in treating patients and preserving their lives, has been accompanied by the emergence of a range of philosophical, ethical, and practical dilemmas linked to a large number of issues with social, economic, and religious dimensions. These issues have given rise to what is known in Western countries as the “right to die”, which some thinkers view as the ultimate expression of liberal discourse based on framing human desires as legally binding rights. Although it is a confounding concept even from the perspective of some of its proponents, it continues to gain ground with confidence in those countries. This paper aims to discuss a number of issues related to illness, treatment, and death, as well as their connection to the development of modern medicine and its immense potential. The paper reviews some Western literature that discusses these issues and their philosophical, ethical, and even religious dimensions, in contrast to most contemporary Arabic literature, which—for reasons I shall outline— has paid little attention to these issues, and is generally limited to a few fatwas and brief discussions that mostly addressed specific questions and did not seek to explore the diversity of the issue and its various ethical dilemmas. This paper does not aim to offer solutions to the issues related to illness, treatment, and death, but rather seeks to identify the fundamental questions and factors necessary for formulating an Islamic perspective on these issues, based on a solid foundation of understanding and critical engagement with their multiple dimensions of the issues related to illness, treatment, and death, as well as the concept of the right to die in its various forms, which differ in the degree of religious, ethical, and philosophical dilemmas they raise. [Perkembangan kedokteran modern, dengan kemampuannya yang luar biasa dalam merawat pasien dan menyelamatkan nyawa mereka, telah disertai dengan munculnya berbagai dilema filosofis, etis, dan praktis yang terkait dengan sejumlah besar isu berdimensi sosial, ekonomi, dan keagamaan. Isu-isu ini telah memunculkan apa yang dikenal di negara-negara Barat sebagai “hak untuk mati”, yang oleh sebagian pemikir dipandang sebagai ekspresi tertinggi dari wacana liberal yang didasarkan pada kerangka pemikiran yang menganggap keinginan manusia sebagai hak yang mengikat secara hukum. Meskipun konsep ini terkesan membingungkan bahkan dari sudut pandang sebagian pendukungnya, konsep tersebut terus mendapatkan penerimaan yang semakin luas di negara-negara tersebut. Makalah ini bertujuan untuk memaparkan dan mendiskusikan sejumlah isu terkait penyakit, pengobatan, dan kematian, serta kaitannya dengan perkembangan kedokteran modern dan potensi besarnya. Makalah ini meninjau beberapa literatur Barat yang membahas isu-isu tersebut beserta dimensi filosofis, etis, dan bahkan religiusnya, berbeda dengan sebagian besar literatur Arab kontemporer yang—karena alasan yang akan kami uraikan—hampir tidak memberikan perhatian pada isu-isu ini, umumnya terbatas pada beberapa fatwa dan pembahasan singkat yang sebagian besar menjawab pertanyaan-pertanyaan spesifik dan tidak berusaha mengeksplorasi keragaman isu tersebut serta berbagai dilema etisnya. Makalah ini tidak bertujuan untuk menawarkan solusi atas isu-isu yang berkaitan dengan penyakit, pengobatan, dan kematian, melainkan berupaya mengidentifikasi pertanyaan-pertanyaan mendasar dan faktor-faktor yang diperlukan untuk merumuskan perspektif Islam mengenai isu-isu tersebut, berdasarkan landasan pemahaman yang kokoh dan keterlibatan kritis terhadap berbagai dimensi isu penyakit, pengobatan, dan kematian, serta konsep hak untuk mati dalam berbagai bentuknya, yang berbeda-beda dalam tingkat dilema keagamaan, etis, dan filosofis yang ditimbulkannya.